A policy review of after‐hours emergency dental care responsibilities. (28th June 2016) - Brecher, Erica A.; Keels, Martha Ann; Quiñonez, Rocio B.; Roberts, Michael W.; Bordley, William Clay
Abstract: Objectives: To examine professional guidelines and/or requirements of state and national dental organizations regarding the responsibility of dentists for after‐hours emergency care. Methods: Guidelines of national dental professional organizations, specialties, and all 50 state dental boards were examined for language pertaining to after‐hours emergency care. Guidelines were categorized as: a) no guidelines; b) deferral to American Dental Association (ADA) guidelines; c) specific guidelines outlined. Results: Most states and national guidelines were similar to the ADA: dentists are obliged to make reasonable arrangements for the emergency dental care of patients of‐record and not‐of‐record. Oral surgery maintains the most stringent guidelines of all specialties. Results of the 50 states reviewed: no guidelines‐16 states (32 percent), deferral to ADA guidelines‐21 states (42 percent), and specific guidelines outlined‐13 states (26 percent). Conclusions: Current after‐hours emergency guidelines are nonspecific and open to interpretation. Variability between state guidelines likely contribute to unnecessary hospital emergency visits and increased healthcare costs, undermining the goal of establishing and maintaining dental homes.